Marketing Strategies of Commercial and Co- Operative Banks: A comprehensive analysis of rural financial institutions and their marketing strategies (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The present ruralfinancial infrastructure comprises a wide variety of formal, semi-formal and informalfinancial service providers, with distinctive cultures and characteristics. Thenumber of organizations and agents is very substantial: 33,553rural andsemi-urban branches of commercial banks, 13,932 rural and semi-urban branchesof Regional Rural Banks, 1.09 lakh primary cooperatives, 1,000 NGO-MFIs andaround 20 MFIs registered as companies and nearly three million SHGs. Even morenumerous are the myriad of informal agents constituting a great range offinancial service providers across the country. Different segments of thefinancial infrastructure have not developed uniformly or simultaneously, andtheir relative standing in terms of government policy and intervention haschanged over time. Moreover, financial institutions have themselves influencedgovernment policy. In the following paragraphs, an attempt is made to trace theforces and compulsions that have led to the development of particular ruralfinancial institutions in the country, to outline the changing fortunes andshares of these different systems, to show the present gap between ruralfinancial needs and provisions, and to assess policy options to reduce this gapthrough institutional development, linkages and reform.